2017
DOI: 10.3390/w10010003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Seawater Desalination in the Management of an Integrated Water and 100% Renewable Energy Based Power Sector in Saudi Arabia

Abstract: This work presents a pathway for Saudi Arabia to transition from the 2015 power structure to a 100% renewable energy-based system by 2050 and investigates the benefits of integrating the power sector with the growing desalination sector. Saudi Arabia can achieve 100% renewable energy power system by 2040 while meeting increasing water demand through seawater reverse osmosis (SWRO) and multiple effect distillation (MED) desalination plants. The dominating renewable energy sources are PV single-axis tracking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 47 publications
0
52
0
Order By: Relevance
“…As a result, the energy consumption of RO for seawater desalination is expected to decrease further and may even go below 2.5 kWh/m 3 . It is indeed reported that 'other new energy recovery systems are under development with the objective of reducing energy consumption for seawater RO (SWRO) below 2 kWh/m 3 [13]. The results below indicate that the cap-ex value of solar-PV-powered RO will decline even further with an efficiency increase in energy consumption as shown in Figure 11.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…As a result, the energy consumption of RO for seawater desalination is expected to decrease further and may even go below 2.5 kWh/m 3 . It is indeed reported that 'other new energy recovery systems are under development with the objective of reducing energy consumption for seawater RO (SWRO) below 2 kWh/m 3 [13]. The results below indicate that the cap-ex value of solar-PV-powered RO will decline even further with an efficiency increase in energy consumption as shown in Figure 11.…”
Section: Resultsmentioning
confidence: 87%
“…The results below indicate that the cap-ex value of solar-PV-powered RO will decline even further with an efficiency increase in energy consumption as shown in Figure 11. new energy recovery systems are under development with the objective of reducing energy consumption for seawater RO (SWRO) below 2 kWh/m 3 [13]. The results below indicate that the capex value of solar-PV-powered RO will decline even further with an efficiency increase in energy consumption as shown in Figure 11.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, the "Mega-Ton Water System" full-scale pilot project operating as part of SWRO research in Japan has been able to reduce energy consumption by 20% by implementing new membrane technologies [39]. Meanwhile, Saudi Arabia, the world's largest producer of desalinated water, is researching the impacts of integrating the demand for desalination with the country's transition to a 100% renewable energy power system by 2050 [40]. Operating a SWRO facility on renewable energy would significantly reduce the environmental impacts associated with the energy requirements for seawater desalination.…”
Section: Discussionmentioning
confidence: 99%